SSR based molecular characterization of brinjal (Solanum melongena) genotypes for quantitative traits - BHATT, LEELA; NAUTIYAL, M K; KUMAR, VIKASH; RICHA (The Indian Journal of Agricultural Sciences, 2022)
The study aimed to evaluate the genetic diversity of eight brinjal (Solanum melongena L.) genotypes including wild species and to develop a molecular profile using 14 SSR primers. The value of the similarity matrix ranged from 0.12–0.87. Dendrogram image is revealing the relationship among eight genotypes of brinjal. The super cluster is divided into two clusters A and B at Jaccard’s similarity coefficient of 0.31. Cluster A again divide into two sub cluster A1 and A2 at Jaccard’s similarity coefficient 0.45. A1 contain three genotypes A1i (SMB-115), A1 ii (BARI), A1 iii (Pant Rituraj) and A2 contain only one genotype (Pusa Upkar) at Jaccard’s similarity coefficient 0.88. Cluster B divided in two sub clusters B1 and B2 at Jaccard’s similarity coefficient of 0.70. B1 again divided into sub cluster B1i (Pant Samrat), B1ii (PB-6) and B2 also divide into two sub cluster B2 i (PB-101) and B2ii (S. gilo) at Jaccard’s similarity coefficient 0.88. Genotype 1 (SMB-115) and 6 (PB-101) were most diverse among all the eight genotypes indicating that the cross between genotype SMB-115 and genotype PB-101 has potential to give more heterotic hybrids due to their highly diverse nature. The results revealed that these microsatellite markers could be used as successful tool to differentiate the genetic makeup of the brinjal crop